2014
DOI: 10.1099/mic.0.070581-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological and genetic factors regulating natural competence in a bacterial plant pathogen

Abstract: For naturally competent bacteria, spatially structured growth can provide an environment for enhanced horizontal gene transfer through transformation and recombination. DNA is often present in the extracellular environment, such as in the extracellular matrix of biofilms, and the lysis of a single cell can result in high local DNA concentrations. Xylella fastidiosa is a naturally competent plant pathogen that typically lives in a surface-attached state, yet previous work characterizing the competence of this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 58 publications
2
36
0
1
Order By: Relevance
“…One of the defective proteins detected was PilQ (strain BBI64), a member of the secretin family that forms the secretin pore of the outer membrane (Collins et al 2001) and is involved in type IV pili biogenesis and importing extracellular DNA into the periplasmic space (Seitz and Blokesch 2013b). Previous studies in X. fastidiosa have demonstrated that pilQ mutants are nonmotile (Meng et al 2005) and noncompetent (Kung and Almeida 2014). Hence, we predict that the insertion in the pilQ coding region is responsible for the lack of twitching and natural competence, as BBI64 is unable to secrete the type IV pili.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the defective proteins detected was PilQ (strain BBI64), a member of the secretin family that forms the secretin pore of the outer membrane (Collins et al 2001) and is involved in type IV pili biogenesis and importing extracellular DNA into the periplasmic space (Seitz and Blokesch 2013b). Previous studies in X. fastidiosa have demonstrated that pilQ mutants are nonmotile (Meng et al 2005) and noncompetent (Kung and Almeida 2014). Hence, we predict that the insertion in the pilQ coding region is responsible for the lack of twitching and natural competence, as BBI64 is unable to secrete the type IV pili.…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlation between recombination frequency and twitching motility was also suggested in our previous study using different media components (Kandel et al 2016). Since components of type IV pili are involved in both natural competence and twitching motility in several naturally competent gram-negative bacteria (Seitz and Blokesch 2013a), including X. fastidiosa (Kung and Almeida 2014), the activity of type IV pili could govern both of these phenomena. On further analysis of competence and pili genes, defective pili genes were detected in the noncompetent strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regions flanking PD1826 were amplified and cloned into pFXFkan [23] using the primers listed in Table S1 (available in the online Supplementary Material) to generate pFXF11 (PD1826 :: kan R ). This suicide vector construct was transformed into X. fastidiosa Temecula1 by exploiting its natural competence [22,24]. Transformed cells were cultured on PWG plates supplemented with kanamycin for 2 to 3 weeks at 28 C. Colonies were screened for loss of PD1826 by PCR using the appropriate primers listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR product was cloned into the chromosomal-based complementation vector pAX1-Cm R [24] at the XhoI and XbaI restriction sites to generate pAX1-CmR/PD1826, which was then transformed into the X. fastidiosa PD1826 knockout strain [22,24]. Recombinant cells were selected on PWG plates supplemented with kanamycin (50 µg ml À1 ) and chloramphenicol (20 µg ml À1 ).…”
Section: Complementation Of the Pd1826-deleted Mutantmentioning
confidence: 99%